Processos de mobilização nos dispositivos midiáticos digitais interativos: estudo de caso do site Moviemobz - Pereira Júnior, José Maria Mendes (2011)
A mobilization is a summoning of wills with a goal, seeking a change in the reality of those who summon it. This process can highlight the essential role of communication as a tool that aims to disseminate information and, above all, promote collectivization. This dual function is now provided by horizontal and constant interaction through interactive digital media devices. So, the central issue of this study aims to seek to understand the changes that shape the way we participate in social life, through the perception of pre-disposition of our society for mobilization processes more participatory and less centralized through these media. Our object of study, limited in MovieMobz, a site / social network where users can conduct mobilizations to watch certain movies that are not easy to distribute in their cities, it helps to reflect on this issue. Thus, the main objective of this work is to make the study of the processes of mobilization in the interactive digital media devices, through a case study of that site. This main objective will be achieved from the following specific objectives: to trace a relational overview between communication and mobilization processes; understand the defining characteristics of these processes of mobilization in digital interactive media: participation through the interconnection in network, the community and interactive collectivization and the questioning through the collective intelligence and, finally, to verify such mobilization processes from the site analysis MovieMobz, our unit case. In this research, therefore, the term "mobilization" is the theme cropping, operated from the inductive-qualitative method with case study of the site mentioned, and participatory research as one of the fundamental operational models. Outlined inside the MovieMobz, or by others social softwares, such as Twitter and Facebook, this mobilization requires a certain number of people to mark a cinema session, which explains a change of pre-filter mentality, where the company determines the productions that would go in theaters each week, to a post-filter dynamic, where the public decide whether or not to watch such movie. But as a business platform, the company is unable to engage individuals to this action of mobilization. This fact must be attributed by lower users' autonomy in decision-making process (questioning), and also by the own motivator, the unequal distribution of films, which may not be cohesive enough to be resolved by collective enterprise, since the social network MovieMobz had little or no interaction (collectivization) and therefore little or no participation. Anyway, the MovieMobz eventually becomes a mirror for future actions of public inclusion in decision-making media process. However, for this process to be doubly successful, we need the community to be effectively motivated and can act with freedom and autonomy.